Safety, Pharmacokinetics, and Pharmacodynamics of the Autotaxin Inhibitor GLPG1690 in Healthy Subjects: Phase 1 Randomized Trials. (23rd April 2019) - van der Aar, Ellen; Desrivot, Julie; Dupont, Sonia; Heckmann, Bertrand; Fieuw, Ann; Stutvoet, Simone; Fagard, Liesbeth; Van de Wal, Karen; Helmer, Eric
Abstract: GLPG1690 is a novel autotaxin inhibitor in development for the treatment of idiopathic pulmonary fibrosis (IPF). We report phase 1 studies investigating the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of GLPG1690 in healthy subjects. We performed a first‐in‐human randomized, double‐blind, placebo‐controlled trial of single (20, 60, 150, 300, 600, 1000, 1500 mg) and multiple (14 days: 150 mg twice daily; 600 and 1000 mg once daily) ascending oral doses of GLPG1690 (NCT02179502), and a randomized, open‐label, crossover relative bioavailability study to compare the PK of tablet and capsule formulations of GLPG1690 600 mg and to assess the effect of food on PK of the tablet formulation (NCT03143712). Forty and 13 subjects were randomized in the first‐in‐human and relative bioavailability studies, respectively. GLPG1690 was well tolerated, with no dose‐limiting toxicity at all single and multiple doses. GLPG1690 was rapidly absorbed and eliminated, with a median tmax and mean t1/2 of approximately 2 and 5 hours, respectively. GLPG1690 exposure increased with increasing dose (mean Cmax, 0.09‐19.01 µg/mL; mean AUC0‐inf, 0.501‐168 µg·h/mL, following single doses of GLPG1690 20‐1500 mg). PD response, evidenced by rapid reduction in plasma lysophosphatidic acid (LPA) C18:2 levels, increased with increasing GLPG1690 plasma levels, plateauing at approximately 80% reduction in LPA C18:2 at around 0.6 µg/mL GLPG1690. Tablet and capsule formulations had similar PK profiles, and no clinically significant food effect was observed when comparing tablets taken in fed and fasted states. The safety, tolerability, and PK/PD profiles of GLPG1690 support continued clinical development for IPF.